Analisis Tingkat Partisipasi Angkatan Kerja di Propinsi Bengkulu (2010-2019) - Neng Murialti; Reza Romanda (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2020)
Bengkulu is a Province in Sumatra which is located at coordinates 5 ° 40 '- 2 ° 0' LS 40 '- 104 ° 0' E with an area of 19,788.70 km2 (7,640.46) which borders: North: West Sumatra, South : Lampung, West: Indian Ocean, East: Jambi and South Sumatra. This study aims to determine the effect of the number of labor force, the number of poor people and the provincial minimum wage on TPAK in Bengkulu province. Of these three variables the number of workforce is positively and significantly related to the TPAK of Bengkulu province, the variable of the number of poor people is positively and not significantly related to the TPAK and the Provincial Minimum Wage is negatively and significantly related to the TPAK in Bengkulu Province.